Gravitational and tectonic stresses in the rock mass and their determination by measurements in separate points - Olovyannyy, A (National Mining University, 2017)
Purpose. Stress state in rock mass is the most important factor affecting processes around mine working. The methods used for calculation of stresses based on hypotheses of elastic thrust, hydrostatic state or spherical equilibrium of the earth crust do not consider tectonic processes and influence of rocks’ viscous properties on formation of stress fields. The goal is to develop methods of calculating stress state in rock masses depending on the elastic and viscous rock properties and interaction of tectonic plates considering stresses measured in individual points. Methods. Conditions of stress state formation in rock masses due to gravitation effect are modeled under axial compression of a cylindrical sample with forbidden lateral movements. Solution of the problem about deformation of such sample allowed to obtain the ratio between lateral stresses and axial stresses. This ratio determines the lateral thrust coefficient in the rock mass. Tectonic component of stress state in rock mass is determined by values of deformations in the horizontal plane caused by interaction of tectonic plates. Tectonic components of stresses depend on tectonic deformations in the horizontal plane. Due to the length of tectonic processes the tectonic component of lateral stresses also depends on viscous and elastic deformations. Findings. Gravitation component of the lateral thrust coefficient does not vary with depth, while the tectonic component is inversely proportional to depth. Growth of lateral thrust coefficient as its measurements are approaching the surface is explained by the effect of tectonic component of stresses. Originality. Experimental measurements of stresses are possible only in a limited number of points. There is no other method to determine stresses in masses with non-horizontal bedding, non-uniformities and folds except for mathematical modeling. Within the frames of hypothesis describing a medium with limited linear viscous deformations, we have obtained equations relating the stress components with full and elastic deformations. The method is developed for formulation and solution of problems for modeling stress state using equations of rock mass state as the medium with quasi-elastic properties. Gravitation component is set by the rocks' weight, and effect of tectonics is set by the tensor of tectonic deformations. Practical implications. A method for solving the problem for determination of stresses in rock mass considering measured stresses in individual points is proposed.

Цель. Напряженное состояние в массиве горных пород является важнейшим фактором, влияющим на процессы вокруг горных выработок. Применяемые методы расчета напряжений, основанные на гипотезах упругого распора, гидростатического состояния или сферического равновесия земной коры, не учитывают тектонические процессы и влияние вязких свойств горных пород на формирование полей напряжений. Ставится цель разработать методы расчета напряженного состояния в массивах горных пород в зависимости от упругих и вязких свойств пород и взаимодействия тектонических плит по замерам в отдельных пунктах. Методика. Условия формирования напряженного состояния в массивах пород от влияния гравитации моделируется при осевом сжатии цилиндрического образца с запрещенными боковыми перемещениями. Из решения задачи о деформировании такого образца получены отношения осевых напряжений к боковым, которые определяют коэффициент бокового распора в массиве горных пород. Влияние вязких свойств пород определяется коэффициентом упругой вязкости, который равен предельной величине отношения вязкоупругих и упругих деформаций. Тектоническая составляющая напряженного состояния массива горных пород определяется величинами деформаций в горизонтальной плоскости, вызванными взаимодействием тектонических плит. В связи с длительностью протекания тектонических процессов тектоническая составляющая боковых напряжений также зависит от вязких и упругих деформаций. Результаты. Гравитационная составляющая коэффициента бокового распора с глубиной не меняется, тектоническая составляющая обратно пропорциональна глубине. Рост коэффициента бокового распора при приближении к поверхности, определенный замерами, объясняется влиянием тектонической составляющей напряжений. Научная новизна. Экспериментальные замеры напряжений возможны лишь в ограниченном количестве точек. Для определения поля напряжений в массивах с негоризонтальным залеганием, с неоднородностями и складками, другого способа, кроме математического моделирования, нет. В рамках гипотезы среды с ограниченными линейно вязкими деформациями получены выражения, связывающие компоненты напряжений с полными и упругими деформациями. Приведен способ постановки и решения задач моделирования напряженного состояния с привлечением уравнений состояния горного массива как среды с квазиупругими свойствами. Гравитационная составляющая задается весом пород, а влияние тектоники – тензором тектонических деформаций. Практическая значимость. Предложен способ решения задачи для определения поля напряжений в массиве пород с учетом замеренных напряжений в отдельных пунктах.

Мета. Напружений стан в масиві гірських порід є найважливішим фактором, що впливає на процеси навколо гірничих виробок. Застосовувані методи розрахунку напружень, засновані на гіпотезах пружного розпору, гідростатичного стану або сферичної рівноваги земної кори, не враховують тектонічні процеси і вплив в’язких властивостей гірських порід на формування полів напружень. Ставиться за мету розробити методи розрахунку напруженого стану в масивах гірських порід в залежності від пружних і в’язких властивостей порід і взаємодії тектонічних плит за вимірами в окремих пунктах. Методика. Умови формування напруженого стану в масивах порід від впливу гравітації моделюється при осьовому стисненні циліндричного зразка із забороненими бічними переміщеннями. З рішення задачі про деформацію такого зразка отримані відношення осьових напружень до бічних, що визначають коефіцієнт бічного розпору в масиві гірських порід. Вплив в’язких властивостей порід визначається коефіцієнтом пружної в’язкості, що дорівнює граничній величині відношення в’язкопружних і пружних деформацій. Тектонічна складова напруженого стану масиву гірських порід визначається величинами деформацій у горизонтальній площині, викликаними взаємодією тектонічних плит. У зв’язку з тривалістю протікання тектонічних процесів тектонічна складова бічних напружень також залежить від в’язких і пружних деформацій. Результати. Гравітаційна складова коефіцієнта бічного розпору з глибиною не змінюється, тектонічна складова обернено пропорційна глибині. Зростання коефіцієнта бічного розпору при наближенні до поверхні, визначеного вимірами, пояснюється впливом тектонічної складової напружень. Наукова новизна. Експериментальні виміри напружень можливі лише в обмеженій кількості точок. Для визначення поля напружень в масивах з негоризонтальним заляганням, з неоднорідностями і складками, іншого способу, окрім математичного моделювання, немає. В рамках гіпотези середовища з обмеженими лінійно в’язкими деформаціями отримані вирази, що зв’язують компоненти напружень з повними і пружними деформаціями. Наведено спосіб постановки і рішення задач моделювання напруженого стану із залученням рівнянь стану гірського масиву як середовища з квазіпружними властивостями. Гравітаційна складова задається вагою порід, а вплив тектоніки – тензором тектонічних деформацій. Практична значимість. Запропоновано спосіб рішення задачі для визначення поля напружень в масиві порід з урахуванням заміряних напружень в окремих пунктах.
Keywords: rocks; stressed state; lateral expansion; tectonic deformations; tectonic stresses; mathematical modeling